KOMUNIKASI PEMBERDAYAAN DISNAKERKOPERINDAG DALAM PENINGKATAN DAYA SAING EKONOMI BANGSA BERWAWASAN GENDER PADA PETANI ANDALIMAN DI KABUPATEN SAMOSIR - simbolon, besti rohana; Panjaitan, Doli Tua Mulia Raja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This research is aimed to know the power of communication of Disnakerkoperindag Samosir Sub-district and its Agent in Increasing the Economic Competition based on Gender in the Andaliman farmer in the Samosir Sub-district. This research apply the Descriptive Qualitative research approach with research informant from the agent of the empower who is the Head of Koperasi Division, Koperasi of Industrial and Commerce, and the chairperson of Samandali Community, including the female Andaliman farmer society. The informant is defined by purposively sampling. The data taken by observation, interview, and documentation. In this research, it is found that DISNAKERKOPERINDAG of Samosir Sub-district had done the communication empowering bsed on gender to the subject of UMKM. Communication empowering used the model of AIDDA. Communication empowering based on gender is successful because of there is an interactional and transactional communication from the AIDDA model of communication. By this empowering, the facilitator is able to communicate with no fear in the social sytem of Batak culture which is formerly it is a taboo to have a close or intense communication in a male instructor to any of his female members finally female farmers could set her self realizing, attention, and motivation to do as what it is instructed by the instructor so that the Andaliman harvest successful.